Controle de Urochloa decumbens e Ipomoea triloba pela associação de herbicidas com palha de cana-de-açúcar - Silva, Ferdinando Marcos Lima; Cavalieri, Sidnei Douglas; Velini, Edivaldo Domingues [UNESP]; Cordeiro, José Guilherme Ferreira; José, Alcebíades Rebouças São (Revista Brasileira de Herbicidas, 2011)
This research aimed to evaluate the efficacy of herbicides associated with sugarcane straw on the control of Ipomoea triloba and Urochloa decumbens after simulation of different time periods of rain. Two experiments were conducted in greenhouse in pots filled with soil, being placed on them the equivalent of 0, 5 and 10 t ha-1 of sugarcane straw, after weed species sowing. The herbicides mesotrione, formulated mixture of [hexazinone+diuron] and imazapic were applied in pre-emergence on the pots with or without straw and with dry soil. At the first experiment, it was simulated a rainfall of 30 mm 1 day after application (DAA), and at the second experiment, the same quantity of rain was simulated 14 DAA. The association of sugarcane straw with the herbicide [hexazinone + diuron] does not alter its efficacy. However, the association of sugarcane atraw with imazapic increase the weed control. For the mesotrione herbicide, the late simulation of rainfall reduced I. triloba control.

Objetivou-se com este trabalho avaliar a eficácia de herbicidas associados com palha de cana-de-açúcar no controle de Urochloa decumbens e Ipomoea triloba, após simulação de diferentes períodos de precipitação pluvial. Dois experimentos foram conduzidos em casa de vegetação, em vasos preenchidos com solo, sendo colocados sobre os mesmos o equivalente a 0, 5 e 10 t ha-1 de palha de cana-de-açúcar, logo após a semeadura das espécies infestantes. Os herbicidas mesotrione, mistura formulada [hexazinone + diuron] e imazapic foram aplicados em pré-emergência nos vasos com ou sem palha e com solo seco. No primeiro experimento, simulouse uma precipitação de 30 mm a 1 dia após a aplicação (DAA), e no segundo a mesma precipitação aos 14 DAA. A associação da palha de cana-de-açúcar com o herbicida [hexazinone + diuron] não altera sua eficácia. Já a associação com imazapic contribui para o aumento do controle das espécies infestantes. Para o herbicida mesotrione, a simulação de precipitação tardia reduziu o controle de I. triloba.
Control of Urochloa decumbens and Ipomoea triloba by the association of herbicides with sugarcane straw
Keywords: Green cane; Saccharum spp.; Weed; Cana crua; Saccharum spp.; Planta daninha